Modern fisheries engineering : realizing a healthy and sustainable marine ecosystem - Bortone, Stephen A.; Otake, Shinya; International Conference on Fisheries Engineering (2019 : Nagasaki-shi, Japan) (Boca Raton, FL : CRC Press, 2020)
Modern Fisheries Engineering: Realizing a Healthy and Sustainable Marine Ecosystem is a compendium of the latest and most cutting-edge information on the diversity of technical aspects associated with Fisheries Engineering. Expanding on presentations given at the International Conference on Fisheries Engineering (ICFE) held in Nagasaki in 2019, it aims to encourage and inspire future generations of young researchers in the field. Topics include artificial reefs, ocean ranching, fishing gear developments, modern monitoring technologies, and other subjects related to the latest practices for conducting efficient, sustainable fishing. This volume brings together world authorities to address a critically important topic, with a fresh and modern approach that includes the latest development in environmental and fisheries science.
Introduction. Fisheries Engineering: Robust Fisheries for Today and Tomorrow. Trends and Obstacles in Artificial Reef Research. Artificial Reefs in France: Current State-of-the-Art and Recent Innovative Projects. Development and Utilization of Artificial Reefs in Korea. The Status of Artisanal Fish Aggregating Devices in Southeast Asia. Design and Creation of Fishing Grounds in Japan with Artificial Reefs. Using Standardized CPUE to Estimate the Effect of Artificial Reefs on Fish Abundance. Using Artificial Substrata to Recover from the Isoyake Condition of Seaweed Beds off Japan. Why do Japanese Fishermen Not Wear Life Jackets? -- Answers Based on Interviews with Fishermen. Habitat-Creation in the Sustainable Development of Marine Renewable Energy. Offshore Wind Energy and the Fishing Industry in the Northeastern USA. Hydrogen Fuel Cell and Battery Hybrid Powered Fishing Vessel: Utilization of Marine Renewable Energy for Fisheries. The Future of Fisheries Engineering.
OCLC-licensed vendor bibliographic record.
Keywords: Fisheries; Fishery management; Marine ecosystem management; SCIENCE / Life Sciences / Biology / Marine Biology; TECHNOLOGY / Fisheries & Aquaculture